2012
DOI: 10.1177/229255031202000213
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the microvascular anastomotic coupler in free tissue transfer

Abstract: T he transfer of autogenous, vascularized free-tissue is a cornerstone of modern reconstructive surgery, particularly when dealing with extensive oncological ablations and large post-traumatic defects. A half-century after Jacobson and Suarez (1) described the first sutured microvascular anastomosis, the cumulative efforts of surgeons and researchers have refined free tissue transfer (FTT) into a reliable modality that often provides excellent cosmetic and functional results.In addition to adequate presurgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 30 publications
(10 reference statements)
5
55
1
5
Order By: Relevance
“…Anastomoses of arteries and veins are usually completed in 22 (arterial anastomosis) and 25 (venous anastomosis) minutes by manual suture, or can be performed in 5 minutes using an anastomotic coupling device for veins. [38][39][40] That is, to perform anastomosis of an artery-vein pair, this procedure requires only an additional 47 minutes with manual suture, or 27 minutes with a coupling device. In fact, at our institution, anastomosis of a primary artery and vein, and an additional artery and vein, required an average of 37 and 42 minutes, respectively, in 15 recent cases (our recorded time includes manipulations under the microscope such as vessel preparation before starting anastomosis).…”
Section: Discussionmentioning
confidence: 99%
“…Anastomoses of arteries and veins are usually completed in 22 (arterial anastomosis) and 25 (venous anastomosis) minutes by manual suture, or can be performed in 5 minutes using an anastomotic coupling device for veins. [38][39][40] That is, to perform anastomosis of an artery-vein pair, this procedure requires only an additional 47 minutes with manual suture, or 27 minutes with a coupling device. In fact, at our institution, anastomosis of a primary artery and vein, and an additional artery and vein, required an average of 37 and 42 minutes, respectively, in 15 recent cases (our recorded time includes manipulations under the microscope such as vessel preparation before starting anastomosis).…”
Section: Discussionmentioning
confidence: 99%
“…3 However, there is considerably less variation in reported venous patency rates with ACD. 3,4 The ACD is thought to improve the consistency of venous anastomoses, 3 and reduce complications. 5 However, no comparative study to date has demonstrated the hypothesized decrease in flap complications.…”
Section: Discussionmentioning
confidence: 99%
“…We agree with previous authors that ACD is consistently faster than hand-sewn strictly in time to complete venous anastomoses. 3,4,8 In our study, we measured total procedure times to reflect system level operative resources. In analyzing re-explorations due to venous insufficiency, times were significantly shorted for flaps performed initially with ACD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly cited advantages of the coupler over suture anastomosis are reduced operative time, reliable vessel eversion, and avoidance of intraluminal thrombogenic material. [1][2][3] However, couplers are more commonly used for venous compared to arterial anastomosis, 4 likely secondary to more favorable vessel characteristics and multiple studies demonstrating suboptimal results in coupled arterial anastomosis. [5][6][7] Flap-related complications are often attributed to errors in microvascular anastomotic technique and include inadequate vessel eversion resulting in luminal exposure of thrombogenic adventitia, uneven suture placement leading to anastomotic leak or stasis, and unrecognized backwalling causing stenosis and thrombosis.…”
Section: Introductionmentioning
confidence: 99%